FOOD CONSUMPTION, NUTRITIONAL AND HEALTH STATUS AMONG FARMER HOUSEHOLDS IN SUBANG, WEST JAVA, INDONESIA - Nani Sufiani Suhanda; Leily Amalia; Khairunisa Khairunisa; Dadang Sukandar (Jurnal Gizi dan Pangan, 2010)
The objectives of this study were : 1) to analyze the consumption of various types of foods (meat, milk, fish, fruit, and others) and the methods of getting the foods among farmer households, 2) To analyze the nutritional status (fathers, mothers and children) among farmer households, and 3) To analyze the health status (fathers, mothers and children) among farmer households. This research was of a retrospective and cross sectional design.This research was conducted in Subang Farming Regency, West Java. There are two types of population (farmer households), namely, those of horticultural region and those of rice field region. The sample size at each location was 261 households, so the total sample was 522 households.  The results of this research show that in general the frequency and quantity of food consumed by the non poor households are relatively better than those of the poor households. Further, as the centers of agricultural production, both regions (rice and horticulture) will produce certain foods in abundance and will affect the patterns of food consumption among the local community and households.  Children’s nutritional status is in general of good category (based on W/A and H/A). Husband’s and wives’ nutritional status is normal. The length of upper respiratory tract infection on wives and children is quite low (<4 days), but among the husbands (non poor households) is quite high (8 days) in the last two weeks. The duration of diarrhea is also low, i.e. only 0-0.2 days in the last two weeks.